2023
DOI: 10.1186/s12913-023-09359-x
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the effectiveness of integrating mental health in HIV programs: a scoping review

Abstract: Introduction Mental health and substance abuse issues are increasing among HIV-positive people, and it negatively impacts health outcomes like engagement, retention in HIV care, and adherence to ART. Thus, national ART programs must include mental health management. The scoping review sought to map evidence on the efficacy of combining HIV and mental health care. Methods The Arksey and O’Malley methodological framework was used to map the existing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 59 publications
(109 reference statements)
0
5
0
Order By: Relevance
“…For instance, one of the facilitators emphasised among health workers and policymakers in Pakistan is the willingness of the health workers to leverage the established HIV mental health services for people with TB. This is an established concept within different countries and HIV facilities [ 46 ], though scarcely documented in the region of study. In our research, the provider of care’s poor counselling capacity and behaviour was stated as a common barrier in India; these factors have been reported to cause delays in the TB care cascade in the country [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, one of the facilitators emphasised among health workers and policymakers in Pakistan is the willingness of the health workers to leverage the established HIV mental health services for people with TB. This is an established concept within different countries and HIV facilities [ 46 ], though scarcely documented in the region of study. In our research, the provider of care’s poor counselling capacity and behaviour was stated as a common barrier in India; these factors have been reported to cause delays in the TB care cascade in the country [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…A need for support for infected children and youth transitioning into young adulthood also emerged from the published research, revealing an unmet need for this expanding group. If we are to achieve the success of the UNAIDS “fourth 90” target, acknowledging the persistence of HIV stigma and integrating mental health services ( 7 ) are some of the first steps aimed at reducing negative perceptions of PLWH and improving HrQoL.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this review reported that health workers in such facilities were more comfortable discussing mental health issues. (Conteh et al, 2023) According to Remien, this integration would strengthen HIV prevention and care and also facilitated global accessibility to mental health services. (Remien et al, 2019) One of the themes that emerged from this current study was that integrating mental care into HIV services has associated challenges.…”
Section: Discussionmentioning
confidence: 99%